Perception and adaptation to climate change of the K'Ho people related to coffee production in Lâm Đồng province, Vietnam - Nguyen Dinh Nghiep; Le Minh Chien; Nguyen Van Hoang; Pham Hong Hai; Dao Thi Hieu; Nguyen Thi Thanh Thuan; Do Van Toan; Le Quang Ngoc; Ho Dieu Huyen (Cogent Social Sciences)
Although the impacts of climate change on agriculture have gained attention, its effects on ethnic minority farming in developing countries remain underexplored. This study examines how the K'Ho people in Lâm Đồng province, Vietnam perceive climate change and adapt their coffee production practices to its challenges. Data were collected from 299 coffee-farming households and through 10 semi-structured interviews with K'Ho individuals and local officials. The findings reveal that the K'Ho people's perception of climate change is reflected through changes in weather phenomena; factors such as temperature, rainfall, wind strength, and sunshine hours are all perceived to be increasing. The K'Ho people recognize substantial changes due to climate change and therefore have various levels of adaptation to continue developing coffee cultivation, including plant level, coffee garden level, landscape level, and household level. Additionally, they have implemented several pest management strategies on coffee plants, such as pesticide spraying, regular pest monitoring, and manual methods (leaf plucking, hand-picking pests). These results provide valuable insights for managers at all levels to support the ongoing development of climate change awareness and adaptation among the K'Ho in agricultural production, thereby contributing to the stable socio-economic development of ethnic minorities in disadvantaged areas.